2014
DOI: 10.4269/ajtmh.13-0647
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Prevalence of Molecular Markers Mediating Antimalarial Drug Resistance in a High Malaria Transmission Setting in Uganda

Abstract: Abstract. Standard therapy for malaria in Uganda changed from chloroquine to chloroquine + sulfadoxine-pyrimethamine in 2000, and artemether-lumefantrine in 2004, although implementation of each change was slow. Plasmodium falciparum genetic polymorphisms are associated with alterations in drug sensitivity. We followed the prevalence of drug resistancemediating P. falciparum polymorphisms in 982 samples from Tororo, a region of high transmission intensity, collected from three successive treatment trials condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
61
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 55 publications
16
61
3
Order By: Relevance
“…We found high rates of two pfmdr1 haplotypes containing mutations previously associated with lumefantrine resistance, NFD and NYD, in isolates from reinfections and recrudescences from the AL arms in both provinces. Our results are consistent with data from Uganda showing selection of the 86N, 184F, and 1246D mutations following treatment with AL (33,34). Malmberg et al recently reported that parasites with the pfmdr1 NFD and NYD haplotypes could tolerate 15-and 7-foldhigher lumefantrine blood concentrations, respectively, than parasites with the YYY haplotype (35).…”
Section: Screeningsupporting
confidence: 82%
“…We found high rates of two pfmdr1 haplotypes containing mutations previously associated with lumefantrine resistance, NFD and NYD, in isolates from reinfections and recrudescences from the AL arms in both provinces. Our results are consistent with data from Uganda showing selection of the 86N, 184F, and 1246D mutations following treatment with AL (33,34). Malmberg et al recently reported that parasites with the pfmdr1 NFD and NYD haplotypes could tolerate 15-and 7-foldhigher lumefantrine blood concentrations, respectively, than parasites with the YYY haplotype (35).…”
Section: Screeningsupporting
confidence: 82%
“…The prevalence of the 4 studied polymorphisms was similar to that in contemporaneous samples from Tororo that were reported previously (43). For two polymorphisms, pfcrt K76T and pfmdr1 N86Y, the prevalence of mutant genotypes was significantly higher in samples from children who had received DP within 30 days than in those from children who had not received DP within 60 days (Table 2).…”
Section: Study Samplessupporting
confidence: 66%
“…Although artemetherlumefantrine is still very effective in malaria treatment in Uganda, 32 analysis of data from different clinical trials showed that high prevalence of wild type Pfmdr-86N parasite genotype is associated with decreased parasite sensitivity to artemisinin-lumefantrine. 29 Furthermore, we found higher prevalence (41.8%) of wild type 76K P. falciparum genotype than a previous study by Mbogo et al 33 that reported 17% in Tororo, Uganda. The variation in the findings could be due to the difference in the study periods.…”
Section: Discussioncontrasting
confidence: 58%
“…In the study by Mbogo et al, 33 samples of previous clinical trials collected between 2002 and 2012 were used in the analysis, which included samples collected when CQ was still a recommended drug in the CQ sulfadoxinepyrimethamine combination, unlike samples collected in 2013 to 2014 used in the current study. The findings of this study in addition to that of Mbogo et al, 33 are however indicative of a steady decline in the prevalence of mutant 76T alleles of the Pfcrt-76 gene in Uganda which had previously peaked at 100% in the population. Studies have shown that it took approximately 8 years (1993 to 2001) since the change in malaria treatment policy for CQ sensitivity to re-emerge in Malawi.…”
Section: Discussionmentioning
confidence: 99%